Insulin Resistance is Associated With Total Bile Acid Level in Type 2 Diabetic and Nondiabetic Population: A Cross-Sectional Study. Issue 10 (March 2016) - Sun, Wanwan; Zhang, Di; Wang, Zhengyi; Sun, Jichao; Xu, Baihui; Chen, Ying; Ding, Lin; Huang, Xiaolin; Lv, Xiaofei; Lu, Jieli; Bi, Yufang; Xu, Qinyi
Abstract : Abstract: Bile acid metabolism was reported to be involved in glucose metabolism homeostasis. However, the exact relationship between bile acid and glucose metabolism as well as insulin sensitivity is not clarified. Therefore, we sought to investigate the association between insulin sensitivity and hyperbileacidemia in type 2 diabetic and nondiabetic population. This community-based cross-sectional study included 9603 residents from Jiading, Shanghai, China, who were 40 years and older. Standardized questionnaire, anthropometric measurements and laboratory tests were conducted. Homeostasis model assessment of insulin resistance (HOMA-IR) ≥ 2.7 was defined as insulin resistance and fasting TBA ≥ 10 mmol/L was defined as hyperbileacidemia. Multivariate stepwise regression analysis revealed that HOMA-IR, age, and male sex were positively associated with hyperbileacidemia in both nondiabetic and diabetic participants. In multivariate logistic models, participants with insulin resistance had significantly higher risk of hyperbileacidemia compared to those who have no insulin resistance, in both nondiabetic and diabetic population (nondiabetic: OR = 1.76; 95% CI 1.42–2.19; P < 0.001; diabetic: OR = 1.56; 95% CI 1.06 – 2.31; P = 0.025, respectively). Further adjustment for the HbA1c level in diabetic population did not change the significant association (OR = 1.59; 95% CI 1.06 − 2.40; P = 0.024). In nondiabetic participants, each 1-unit increment of HOMA-IR conferred an 18% higher risk of hyperbileacidemia (95% CI 1.04–1.35; P = 0.013), whereas in diabetic participants, this association was similar but not significant (95% CI 0.95–1.59; P = 0.117). Insulin resistance was positively associated with hyperbileacidemia in both nondiabetic and diabetic population. The increase in the bile acid level in insulin-resistant population regardless of status of diabetes and glucose level indicated the important role of insulin resistance in the regulation of bile acid metabolism in human.